The Politics of the European Green Deal: Environmental Sustainability and Economic Transformation (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The European Green Deal is one of the most ambitious policy agendas that will help the European Union become sustainable and climate-neutral economy by as early as 2050. The paper has explored the political aspects of the Green Deal, considering how the aims of environmental sustainability interlock with economic change and political struggle in the European Union. The key question of the present research lies in the capacity to find a compromise between the safety of the environment and the competitiveness of industries, as well as between the distributional justice and the social transparency. This article is going to adopt a qualitative approach of analysis using policy papers, institutional reports, and available scholarly literature that discusses the creation, implementation, and identification of the Green Deal. The findings also suggest that despite the fact that the strategy has seen an increase in funding towards green technology, sustainable infrastructure, as well as renewable energy, it has also contributed to the political conflicts between the member states as they hold diverse economic interests and capabilities. A transition that is equitable and fair across the board during the green transition is not easily attained hence industrial players as well as labour markets are subjected to intense transitional problems. The report identifies disparity in policy goals and implementation actuals especially in the areas of funding, readiness of technology, and coordination of governance. Nevertheless, the European Green Deal turns out to be a key tool towards making the EU the leader in climate laws globally. The conclusion of the article is that the success of the initiative will be determined by the continuation of the political power, flexibility of the policy machinery and the fair sharing of costs and rewards. This information can be useful for shaping sustainability policies worldwide in the future.